Damping torque coefficient analysis of PMSG-based WT with VSG control considering wind turbine dynamics - Qu, Tong (2022)
This paper expands the damping torque coefficient analysis (DTCA) for studying the small-signal stability of permanent magnet synchronous generator (PMSG)-based wind turbine (WT) under virtual synchronous generator (VSG) control with consideration of WT dynamics. Firstly, the typical VSG is implemented in the grid-side voltage source converter (GSVSC), which enables selfsynchronization without phase-locked loop (PLL). The maximum power point track (MPPT) algorithms are utilized to give the power reference for VSG. Then, the corresponding inertia and damping support can be provided by the kinetic energy of PMSG. Based on the established model, the DTCA is analytically conducted to not only reveal the key factors that influence the WT stability but also provide guidance for parameter tuning. As a result, it is important to find that the WT dynamics impair the damping and even lead to system instability. Moreover, the minimum value of VSG damping control parameter is analytically given to ensure the system stability under any load below the rated wind speed. Finally, the case studies considering one single PMSG connected to a large grid with and without inclusion of WT dynamics are performed and compared to demonstrate the accuracy of the proposed model and evaluate the applications of DTCA.